Survey of some viruses transmitted through seeds of Bean and Pea in Lattakia province-SYRIA - Abbas, Noura; Darwish, Youla (Latakia University Journal -Biological Sciences Series, 2018)
Results of this search indicates that, the 374 samples of seeds; TEMA-Beans and Pea-America and Pea-Holland; carried BYMV, BBMV and PSbMV. The heights percentage of seed transmission was 11.5% for PSbMV in tested samples, Seed transmission of PSbMV varied among the kind of tested seed (TEMA-Beans 11.6%; Pea-Holland 9.80% and Pea-America 7.92%). Seed transmission of BBSV was recorded in 8.19% in tested samples, and was recorded only in TEMA-Beans in high percentage (24.16%). Seed transmission of BBMV was recorded in 5,7% in tested samples with the heights percentage(10.%) in TEMA-Bean seeds, and was not recorded in Pea-America seeds where as recorded in Pea-Holland seeds (4.5%). التحرّي عن بعض الفيروسات المنقولة في بذور البازلاء والفاصولياء المباعة في محافظة اللاذقية-سورية أشارت نتائج البحث إلى حمل بذور الفاصولياء – تيما والبازلاء - الأمريكية والبازلاء- الهولندية والبالغة (374) عينة لفيروسات الموزاييك الأصفر للفاصولياء (BYMV) وتبرقش الفول (BBMV) وموزاييك البازلاء المنقول بالبذور(PSbMV). كانت أعلى نسبة انتقال لفيروس موزاييك البازلاء المنقول بالبذور( 10.5%) في مجموع العينات المختبرة. وقد تباينت نسبة انتقاله حسب نوع العينة حيث كانت الأعلى في بذور الفاصولياء- تيما (11.6%) وحسب اختلاف مصدر العينة كما هو مبين في حالة بذور البازلاء (9.80% في البذور الهولندية و 7.92% في البذور الأمريكية). أمّا فيروس الموزاييك الأصفر للفاصولياء فقد سُجّل بنسبة انتقال 8.19% من مجموع العينات المختبرة والتي لم يُسجّل فيها الفيروس سوى في بادرات الفاصولياء-تيما وبنسبة مرتفعة (24.16%). وسُجّل انتقال فيروس تبرقش الفول بنسبة 5.7% فقط في البذور المختبرة وجاءت أعلى نسبة انتقال له في بذور الفاصولياء- تيما (10%), ولم يُسجّل انتقاله في بذور البازلاء الأمريكية في حين سُجّل انتقاله في بذور البازلاء الهولندية بنسبة 4.5%.